Management of Inflammatory Rheumatologic Diseases with Orthoses - Taciser Kaya (Archives of Rheumatology, 2009)
An orthosis is a device applied to the body externally to relieve pain, stabilize or immobilize, prevent or correct deformity, improve function, positioning, supporting and asist weak muscles. It can be applied to any part of the body, such as the hand, elbow, shoulder, head, neck, back, hip, knee, ankle and foot. As part of the comprehensive management of rheumatoid arthritis (RA) and related conditions, orthoses may be recommended to treat symptoms of the disease and improve performance of everyday activities. However orthosis prescription is not a simple process; clinicians and patients need to work together to determine the daily wear pattern that maximizes benefit and minimizes inconvenience according to the patients’ individual needs. Besides, patients wearing orthoses should be instructed about daily and total usage duration, necessitating orthosis wearing tasks, hygienic rules and to avoid undesirable effects of orthosis usage. In this manuscript, the articles relating orthosis usage in inflammatory rheumatologic diseases have been reviewed. (Turk J Rheumatol 2009; 24: 46-50)